Education for Sustainability in Business Economics: Challenges and Experiences - Aparicio de Castro, Gloria; Catalán Martínez, Elena; Maseda, Amaia (Journal of Management and Business Education, 2023)
Recognizing the imperative to forge alliances with other universities and share experiences with peers in our field, facilitating continued progress in the development of specific pathways for Economics and Business studies, this special issue of the Journal of Management and Business Education (JMBE) has emerged. The title itself serves as a manifesto of purpose: Education for Sustainability in Business Economics: Challenges and Experiences. The six papers comprising this special issue of JMBE analyze specific cases and practical experiences that illustrate the integration of sustainability into the educational strategies of various academic centers and university programs in Spain. They explore the challenges, experiences, and opportunities arising from the intersection of sustainability and education in Economics and Business in a world increasingly cognizant of the importance of achieving equitable, socially responsible, and environmentally friendly economic development. The selected papers delve into the tools, methods, and educational models that have emerged to equip students in the field of Economics and Business with the knowledge and skills necessary to confront the intricate challenges posed by sustainability today. Pedagogical strategies, tools, and educational methodologies that can be employed to promote a profound understanding of sustainability principles in the economic and business context are also explored. This encourages a holistic vision that encompasses economic, social, and environmental aspects in corporate decision-making.